(untitled) - Gibson, Greg (Sunderland, Mass., 2004)
A Primer of Genome Science bridges the gap between standard genetics textbooks and highly specialized, technical, and advanced treatments of the subdisciplines. It provides an affordable and up-to-date introduction to the field that is suited to advanced undergraduate or early graduate courses. Bioinformatic principles and experimental strategies are explained side-by-side with the experimental methods, establishing a framework that allows teachers to explore topics and the literature at their own pace.
Keywords: Genetics,Di truyền học